Upaya Pengendalian Faktor Resiko PTM (Penyakit Tidak Menular) - Purwati Purwati; Alfi Noviyana; Dea Roudhotul (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2020)
Problems in general in Banyumas district related to non-regular diseases are: lack of health education, lack of knowledge and skills of cadres, lack of community support, and low visits by elderly / target groups. Posbindu in Pamijen village is implemented with integrated posyandu activities for toddlers where the activities are still limited to monitoring blood pressure and treating minor illnesses, while counseling activities from health workers are rarely carried out. This condition has made the mothers of the Asyiyah Pamijen branch not yet moved to join Posbindu. Apart from that, the Posbindu cadres were not ready and skilled. The method of solving problems implemented in this community service is by providing IEC (Communication, Information and Education) in the form of material about Non-Communicable Diseases (PTM) and risk factors and efforts to control PTM risk factors. PTM activities in Pamijen village involve Aisyiyah's organization as an organization that is active in the community to follow up on the Ministry of Health program so that the program can run as expected. The follow-up of this activity is carried out at the Posbindu activity in Pamijen village which is carried out routinely every 1 month. There is an increase in knowledge about PTM in Aisyiyah cadres in Pamijen village so that Aisyiyah cadres can recognize PTM on their own and educate the public to recognize PTM.